Lysine-Binding Heterogeneity of Lp(a): Consequences for Fibrin Binding and Inhibition of Plasminogen Activation - Leerink, C Bas; Duif, Pieter F C C M; Gimpel, Joke A; Kortlandt, Wouter; Bouma, Bonno N; Rijn, Herman J M van (Thrombosis and Haemostasis, 1992)
Lipoprotein(a) [Lp(a)] is recognized as an independent risk factor for atherosclerosis. Lp(a) consists of a LDL-like moiety with an additional glycoprotein, apo(a), linked to apolipoprotein B-100. Apo(a) has a high homology with plasminogen (Pg). In vivo, Pg is activated on a fibrin surface by tissue Pg activator (tPA). We prepared Lp(a) from plasma by sequential ultracentrifugation followed by lysine-sepharose affinity chromatography. We found that a changing (donor dependent) fraction of the Lp(a) did not bind to lysine-sepharose. This fraction, designated Lp(a)lys–, was further purified using gel filtration. Bound Lp(a) [Lp(a)lys+] was eluted with 0.2 M EACA. Apo(a) isoforms in both fractions were identical. In contrast Lp(a)lys+ inhibited Pg activation by tPA in vitro (IC50% 20 mg/1), whereas Lp(a)lys– did not. In addition Lp(a)lys– did not bind to CNBr-digested fibrinogen whereas Lp(a)lys+ did (Kd,app = 0.2 nM). Therefore we conclude that a changing donor dependent fraction of human plasma Lp(a) does not inhibit Pg activation in vitro and does not bind to CNBr-digested fibrinogen.